Complete Freund's adjuvant‐induced reduction of exploratory activity in a novel environment as an objective nociceptive endpoint for sub‐acute inflammatory pain model in rats. (2nd March 2015) - Zhu, C.Z.; Bannon, A.W.; Joshi, S.K.
Abstract Background Hind paw injection of complete Freund's adjuvant (CFA) is a commonly used sub‐acute inflammatory pain model in rodents with typical subjective endpoint measurements of paw withdrawal to thermal or mechanical stimuli. Methods Here, we assessed CFA‐induced reduction of exploratory activity in a novel environment (CRANE) as an objective nociceptive endpoint in rats. CFA (50%) was subcutaneously injected into the plantar aspect of the hind paw either unilaterally or bilaterally (150 μL/paw). Exploratory activity was recorded using an automated locomotor activity system. Results Bilateral CFA injection reduced exploratory activity 4–48 h following injection, compared to sham controls. Unilateral CFA injection produced less reduction of exploratory activity, compared to bilateral injection. Effects of orally dosed standard analgesics on CRANE were examined 48 h following bilateral CFA injection. Diclofenac treatment produced dose‐related reversal of CRANE at 0.03–1.0 mg/kg with a plateau effect observed at higher doses (up to 30 mg/kg). Ibuprofen also produced dose‐related reversal CRANE at 0.3–3.0 mg/kg with a plateau effect at higher doses (up to 60 mg/kg). Similarly, celecoxib produced dose‐related reversal CRANE at 3–10 mg/kg, but not 30 mg/kg. Gabapentin (up to 100 mg/kg) and duloxetine (up to 30 mg/kg) produced no reversal of CRANE. Conclusions The results presented here demonstrate that CRANE provides an objective assessment of pain behaviours for sub‐acute inflammatory pain in rats. The pharmacological profile of standard analgesics supports that CRANE model may potentially be used to identify novel analgesic agents for the treatment of sub‐acute inflammatory pain.